Differential effects of central fructose and glucose on hypothalamic malonyl–CoA and food intake - Cha, Seung Hun (National Academy of Sciences, 2008)
The American diet, especially that of adolescents, contains highly palatable foods of high-energy content and large amounts of high-fructose sweeteners. These factors are believed to contribute to the obesity epidemic and insulin resistance. Previous investigations revealed that the central metabolism of glucose suppresses food intake mediated by the hypothalamic AMP-kinase/malonyl–CoA signaling system. Unlike glucose, centrally administered fructose increases food intake. Evidence presented herein indicates that the more rapid initial steps of central fructose metabolism deplete hypothalamic ATP level, whereas the slower regulated steps of glucose metabolism elevate hypothalamic ATP level. Consistent with effects on the [ATP]/[AMP] ratio, fructose increases phosphorylation/activation of hypothalamic AMP kinase causing phosphorylation/inactivation of acetyl–CoA carboxylase, whereas glucose has the inverse effects. The changes provoked by central fructose administration reduce hypothalamic malonyl–CoA level and thereby increase food intake. These findings explain the paradoxical fructose effect on food intake and lend credence to the malonyl–CoA hypothesis.